Virulence Genes and Antimicrobial Resistance Profiles of Pasteurella multocida Strains Isolated from Rabbits in Brazil. (31st July 2012) - Ferreira, Thais Sebastiana Porfida; Felizardo, Maria Roberta; Sena de Gobbi, Débora Dirani; Gomes, Cleise Ribeiro; Nogueira Filsner, Pedro Henrique de Lima; Moreno, Marina; Paixão, Renata; Pereira, Jucélia de Jesus; Micke Moreno, Andrea
Abstract : Pasteurella multocida is responsible for a wide range of diseases in domestic animals. In rabbits, the agent is related to nasal discharge, pneumonia, otitis media, pyometra, orchitis, abscess, and septicemia. One hundred and forty rabbits with respiratory diseases from four rabbitries in São Paulo State, Brazil were evaluated for the detection of P. multocida in their nasal cavities. A total of twenty-nine animals were positive to P. multocida isolation, and 46 strains were selected and characterized by means of biochemical tests and PCR. P. multocida strains were tested for capsular type, virulence genes, and resistance profile. A total of 45.6% (21/46) of isolates belonged to capsular type A, and 54.34% (25/46) of the isolates were untypeable. None of the strains harboured toxA or pfhA genes. The frequency of the other twenty genes tested was variable, and the data generated was used to build a dendrogram, showing the relatedness of strains, which were clustered according to origin. Resistance revealed to be more common against sulfonamides and cotrimoxazole, followed by erythromycin, penicillin, and amoxicillin.